Liquid helium level regulation improvement in the LHC electrical distribution feedboxes. Issue 1 (1st May 2022) - Bradu, B; Coppier, H; Gery, J; Pezzetti, M; Tovar, A
Abstract: An important cryogenic equipment of the Large Hadron Collider (LHC) consists in the electrical distribution feedboxes (DFBs) which are used to power the superconducting magnets of the accelerator. These feedboxes contain the current leads achieving the electrical transition between the copper cables at ambient temperature to the Niobium-Titanium wires at cryogenic temperature, immersed in a liquid helium bath at 4.5 K. This liquid helium bath must be regulated at a defined level to allow the powering of the LHC, and this regulation often caused non-availabilities in the past. This paper presents the development of a new control scheme, coupled to the existing PID level controller, significantly improving this regulation, and rejecting disturbances in a highly efficient manner. First, a dynamic model of the DFBs was developed in the EcosimPro software using the CRYOLIB library to reproduce in simulation the regulation issues. In a second step, the new proposed regulation modes were tested and validated in simulation. Finally, the paper will present the results obtained in 2021 on a real DFBs operation in the LHC, validating the new control approach prior its massive deployment all around the LHC cryogenics.